Opposing inflammatory biomarker responses to sleep disruption in cancer patients before and during oncological therapy - Oliva, Delmy; Andersson, Bengt-Åke; Lewin, Freddi; Jensen, Lasse D. (Frontiers in Neuroscience, 2022)
Background: Sleep disruption is known to be highly prevalent in cancer patients, aggravated during oncological treatment and closely associated with reduced quality of life, therapeutic outcome and survival. Inflammatory factors are associated with sleep disruption in healthy individuals and cancer patients, but heterogeneity and robustness of inflammatory factors associated with sleep disruption and how these are affected by oncological therapy remain poorly understood. Furthermore, due to the complex crosstalk between sleep-, and therapy-associated factors, including inflammatory factors, there are currently no established biomarkers for predicting sleep disruption in patients undergoing oncological therapy. Methods: We performed a broad screen of circulating biomarkers with immune-modulating or endocrine functions and coupled these to self-reported sleep quality using the MOS sleep scale. 90 cancer patients with gastrointestinal, urothelial, breast, brain and tonsillar cancers, aged between 32 and 86 years, and scheduled for adjuvant or palliative oncological therapy were included. Of these, 71 patients were evaluable. Data was collected immediately before and again three months after onset of oncological therapy. Results: Seventeen among a total of 45 investigated plasma proteins were found to be suppressed in cancer patients exhibiting sleep disruption prior to treatment onset, but this association was lost following the first treatment cycle. Patients whose sleep quality was reduced during the treatment period exhibited significantly increased plasma levels of six pro-inflammatory biomarkers (IL-2, IL-6, IL-12, TNF-a, IFN-g and GM-CSF) three months after the start of treatment, whereas biomarkers with anti-inflammatory, growth factor, immune-modulatory, or chemokine functions were unchanged. Conclusions: Our work suggests that biomarkers of sleep quality are not valid for cancer patients undergoing oncological therapy if analysed only at a single timepoint. On the other hand, therapy-associated increases in circulating inflammatory biomarkers are closely coupled to reduced sleep quality in cancer patients. These findings indicate a need for testing of inflammatory and other biomarkers as well as sleep quality at multiple times during the patient treatment and care process.